1998
DOI: 10.1111/j.1398-9995.1998.tb03916.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seasonal exposure to pollen on nonspecific interleukin‐4, interleukin‐5, and interferon‐gamma in vitro release by peripheral blood mononuclear cells from subjects with pollinosis

Abstract: The immune response to environmental allergens depends on both genetic and environmental factors. Allergen exposure triggers the activation of allergen-specific Th2 cells in allergic patients, as well as increased Th2-type cytokine mRNA expression and eosinophil recruitment. Nevertheless, different patterns of release of cytokines could explain the heterogeneity of atopic response. In our study, 25 patients with pollinosis and 15 healthy donors were selected to characterize their release of Th2 (interleukin [I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Initially after start of IT, the production of Th2-like cytokines decreased. This early decrease seen already after 2 weeks of treatment might either be a consequence of migration of peripheral T cells to the site of local in¯ammation owing to the allergen injections, or perhaps more likely, owing to a natural decrease in Th2-type cytokines from the last pollen season [23,24]. According to our experiences, the IL-4 and IL-5 levels were still relatively high when the IT started in the autumn.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Initially after start of IT, the production of Th2-like cytokines decreased. This early decrease seen already after 2 weeks of treatment might either be a consequence of migration of peripheral T cells to the site of local in¯ammation owing to the allergen injections, or perhaps more likely, owing to a natural decrease in Th2-type cytokines from the last pollen season [23,24]. According to our experiences, the IL-4 and IL-5 levels were still relatively high when the IT started in the autumn.…”
Section: Discussionmentioning
confidence: 55%
“…IL-12 is believed to be an important regulator of the Th1/Th2 balance of immune responses (reviewed in [29]). There are also indications that allergen exposure during pollen season has a nonspeci®c priming effect on the Th2-type cytokine production by PBMC in vitro [23,24]. Other studies have shown that low allergen doses lead to an immune response of Th2 type, while high doses results in a Th1-type response [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro allergen stimulation [18] and allergen challenge in allergic subjects result in an increase in the IL4/IFN‐γ ratio in PBMNC [19]. Munoz‐Bellido et al [1] reported similar results from polyclonally stimulated PBMNC during natural pollen exposure, while another group observed an increased release of IL‐4 but unchanged IFN‐γ production [20]. In contrast, one investigation utilizing flow cytometry to measure the numbers of IL‐4‐ and IFN‐γ‐producing CD4 + and CD8 + lymphocytes found no seasonal variation [21].…”
Section: Discussionmentioning
confidence: 99%
“…One additional study showed that the cumulative dose provocation regimen can induce a more pronounced Th2‐like immune response in asthmatic patients than the low dose provocation model (43). The effect on T cell activation of natural pollen exposure during the relevant season was studied in allergic patients, and most of these studies showed a seasonal increase of Th2 cytokines with no variation or a decrease of IFN‐ γ (44–48).…”
Section: Specific Challengesmentioning
confidence: 99%